Determinación de zonas susceptibles a erosión hídrica en los cantones de Macará y Celica de la provincia de Loja, utilizando sistemas de información geográfica y teledetección - Ramos Cueva, Alexis Mauricio (2016)
The importance of conserve a soil of good quality is essential, for agricultural systems, the maintenance of ecosystems and for our survival. It identified the areas susceptible to hydric erosion employing the RUSLE model through geographic information systems and remote sensing, as a tool for generating basic information on the implementation of strategies of soil conservation resource. It generated the information about the erosive power of the rain (with monthly precipitation data), the erodibility of the soils (determining the structure, permeability, texture, fine sand and organic material), the vegetable cover, the topography, and the management practices, proposing finally alternatives of reducing of the erosion in the most critical places. The 12,43 % that corresponds to 17 398.42 of the total area, it presented, losses of soil higher to 200 t/ha/year (very high), while that the 67,73 %, that is to say 86 417.72 showed lower losses to 10 t/ha/year (swift). The areas of greatest susceptibility to hydric erosion are located on the 63,98 % of the Pindal canton and in small sites of Zapotillo in the parish of Paletillas, due to the presence of annual crops and perennial, which have low capacity to prevent the impact of rainwater on the ground, when implanted in places with slopes greater than 20,6 % and for presenting clayey textures with low content of organic material in most soils. As main measure of mitigation of erosion it raised the tilling along contour bunds on maize crops, with the erosion was reduced in a 50 % in the most susceptible areas, conditions that can be taken into account in plans action of each locality.